EXPLORING GENERATION Z’S METHODS OF LEARNING ENGLISH PRONUNCIATION THROUGH TIKTOK - Fadilah, Nur; Zainuddin, Moh.; Zumrudiana, Ainu; Lestari, Iin Widya (Journal of English Language and Culture, 2025)
This research explores how Generation Z perceives learning English pronunciation using the social media platform TikTok.  Generation Z is known for its familiarity with technology and social media, including TikTok, which is incredibly popular among them. The main objective of this research is to understand how Generation Z perceives and engages with TikTok as a tool for learning English pronunciation, as well as the challenges and opportunities they encounter. The participants in this study were 10th-grade students from SMKN 3 Bojonegoro who were studying PSPT 1 and 2. The research utilized a qualitative approach, combining questionnaire surveys and in-depth interviews to gather comprehensive data on the students' experiences with using TikTok videos to learn English pronunciation. The results revealed that TikTok is a preferred platform for students to practice English, with 58.6% of students feeling comfortable using TikTok for pronunciation practice. Additionally, 63.8% of students stated that TikTok boosted their self-confidence in practicing English pronunciation. The platform offers opportunities for students to practice English in a relaxed, flexible, and engaging manner, thereby increasing motivation. However, the study also identified some challenges and obstacles faced by students, such as being easily distracted by entertainment content, which can lead to a lack of focus, as well as a lack of direct feedback for error correction. In conclusion, this research suggests that TikTok can be an effective tool for Generation Z to learn English pronunciation, as long as engaging and collaborative content is utilized. It is hoped that these findings will contribute to the development of more modern and interactive language learning methods on digital platforms like TikTok.